2018
DOI: 10.1002/ddr.21463
|View full text |Cite
|
Sign up to set email alerts
|

Determination of permeability, plasma protein binding, blood partitioning, pharmacokinetics and tissue distribution of Withanolide A in rats: A neuroprotective steroidal lactone

Abstract: Preclinical Research & Development Withanolide A (WA), a steroidal lactone is a major bioactive constituent of Withania somnifera (L.) with remarkable neuropharmacological activity. In this study, we investigated the permeability, plasma protein binding (PPB), blood partitioning, intravenous (i.v.), and oral pharmacokinetics as well as i.v. tissue distribution (TD) of pure WA in a rat model. The PPB, RBCs partitioning, and permeability of WA were determined by Ultra Performance Liquid Chromatography (UPLC) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The low VDss might suggest plasma protein binding (PPB) and this phenomenon influences the absorption, biodistribution, metabolism, and excretion of drugs. In silico results of our study also corroborate with the one performed by Singh et al [43] in which withanolide A from Withania somnifera (L.), with neuropharmacological activity, presented high PPB, passive permeability and a fast and wide distribution kinetics in vitro. Also, Dubay et al [44] demonstrated that withanolides and withanosides of W. somnifera have a strong binding to serum albumin.…”
Section: Discussionsupporting
confidence: 92%
“…The low VDss might suggest plasma protein binding (PPB) and this phenomenon influences the absorption, biodistribution, metabolism, and excretion of drugs. In silico results of our study also corroborate with the one performed by Singh et al [43] in which withanolide A from Withania somnifera (L.), with neuropharmacological activity, presented high PPB, passive permeability and a fast and wide distribution kinetics in vitro. Also, Dubay et al [44] demonstrated that withanolides and withanosides of W. somnifera have a strong binding to serum albumin.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma bioavailability of withaferin A was also shown in rats after oral administration of a polyherbal formulation containing WS root [ 147 ]. Plasma PK of withanolide A was established in rats following oral administration of the compound, which also showed wide tissue distribution; notably, brain levels were considerably lower than in lung, kidney, liver, heart, and spleen [ 148 ]. Four major withanamides were detected in the mouse brain following the intraperitoneal administration of an extract of WS [ 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pharmacokinetic data of withanolides should be taken seriously. Recently, several pharmacokinetic studies of individual withanolides have been reported, which demonstrated that the low bioavailability of this type of bioactive molecules limited their clinical application. Employing the Madin‑Darby canine kidney cell culture system, the absorption characteristics of several withanolides have been investigated, and different results have been observed.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In this study, withanolides were diluted in Hank's buffered saline and tested for permeability by the SinoVeda's cell culture system; withanone, 1,2‐deoxywithastramonolide, and withanolides A and B were highly permeable; withanosides IV–V were low permeable; however, withaferin A ( 13 ) was either impermeable or metabolized on passing through the cell layer . Furthermore, the pharmacokinetic profiles of withanolide A were also assessed using Sprague Dawley rats; very low concentration in plasma and poor bioavailability in orally administered rat have been found . It is reported that 13 could be rapidly removed either in male rat or in human liver microsomes after oral administration; the first‐pass metabolism of 13 may be a major obstacle to good oral bioavailability in male rats and humans .…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%